Changing Epidemiology of Catheter-Related Bloodstream Infections in Cancer Patients. (17th May 2018) - Chaftari, Anne Marie; Hachem, Ray; Jiang, Ying; Shah, Pankil; Hussain, Alawami; Hamal, Zainab Al; Yousif, Ammar; Jordan, Mary; Michael, Majd; Raad, Issam
Abstract : We compared the etiologic organisms of bloodstream infections (BSIs) in cancer patients with central venous catheters (CVCs) between 2 cohorts separated by more than a decade. Gram-negative organisms have become the predominant etiologic organisms of BSIs (52%); they now contribute to 41% of catheter-related BSIs (CRBSIs). Infect Control Hosp Epidemiol 2018;39:727–729